Synthesis of high quality CuO nanoflakes and CuO–Au nanohybrids for superior visible light photocatalytic behavior. Issue 85 (30th August 2016) - Zhang, Xinyu; Yang, Yawei; Que, Wenxiu; Du, Yaping
Abstract : High-quality CuO nanoflakes and CuO–Au nanohybrids are synthesized by a facile wet chemistry strategy. Compared with pure CuO nanoflakes, CuO–Au nanohybrids exhibit superior visible light-driven photocatalytic performance and have a higher photocurrent density (46 mA cm −2 ). Abstract : Well-defined CuO nanoflakes and CuO–Au nanohybrids are successfully obtained by a facile but effective wet chemistry synthesis method. Compared with CuO nanoflakes, the formation of high-quality CuO–Au nanohybrids can improve the visible light absorption efficiency, charge generation and separation efficiency through surface plasmon resonance (SPR), thus yielding remarkably enhanced photoelectrochemical and photocatalytic activities. CuO–Au nanohybrids with an optimized Au nanoparticle loading concentration (10 wt%) and particle size (∼15 nm) present the highest photocurrent density (46 μA cm −2 ) and degradation rate constant ( k = 0.64 h −1 ), which are almost ∼4 times higher than those of the CuO nanoflakes. The high photocatalytic properties and robust synthesis of CuO–Au nanohybrids can expand new material systems for the visible light utilization of solar energy and effective treatment of organic pollutants.